Belief in science-related conspiracy theories is not just a matter of knowledge: The democratic quality of countries as a protective factor - Irene López-Navarro; Libia Santos-Requejo (PLoS ONE, 2025)
Concerns regarding the increasing prevalence of conspiracy theory beliefs are growing in public discourse. This study investigates science-related conspiracy theories due to their significant potential impact on individual and global health. Using data from a Special Eurobarometer survey (n = 37,079), our research demonstrates the importance of considering public perceptions of science when trying to understand the acceptance of such conspiracy theory beliefs. They are strongly associated with mistrust in scientists and lower level of knowledge. But there is a key factor at the country level, the quality of democracy, which plays a protective role against the acceptance of unwarranted beliefs. Even individuals with lower levels of knowledge or greater mistrust of scientists are less likely to believe in science-related conspiracy theories if they live in democratic countries than in authoritarian states.